Transanal total mesorectal excision vs intersphincteric resection for low rectal cancer: a propensity-score matching study - Li Zhengbiao; Feng Qingbo; Wang Xingqin; Xu Fujian; Wang Qi; Huang Yong; Xie Ming (结直肠肛门外科)
[Objectives] To compare the clinical effectiveness between transanal total mesorectal excision (taTME) and intersphincteric resection (ISR) for low rectal cancer. [Methods] This was a retrospective analysis of 122 patients with low rectal cancer treated at our hospital between January 2016 and April 2021. Sixty-one patients underwent laparoscopic ISR (ISR group), and 61 underwent laparoscopic taTME (taTME group). After propensity-score matching, 38 patients were included in each group. The following data were compared between the two groups: surgical parameters, pathology findings, postoperative recovery, postoperative complications, postoperative anal function, and postoperative quality of life. [Results] All surgeries were uneventful, and there were no intraoperative complications. In the taTME group, the mesorectum was completely or nearly completely resected. The two groups did not differ significantly with regard to operation time, intraoperative blood loss, anastomosis-anus distance, protective stoma rate, distal resection margin length, positive circumferential resection margin rate, positive distal resection margin rate, and lymph node yield (P>0.05). The time to remove the catheter was significantly longer in the taTME group than in the ISR group(P<0.05). Time to the removal of drains, time to first postoperative flatulence or bowel movement, time to resuming semi-liquid diet, time to off-bed activities, postoperative hospitalization, re-admission rate within 30 days postoperative, and overall complication rate within 30 days postoperative were not significantly different between the two groups (P>0.05). The median follow-up duration was 30 months for the ISR group and 21 months for the taTME group. Wexner anal incontinence score was comparable between the two groups (P>0.05). Using the European Organization for Research and Treatment of Cancer quality of life questionnaire (EORTC QLQ-C30), the taTME group had significantly higher physical function score in the functional scales and lower diarrhea score in the single measurement scales than the ISR group (P<0.05). Using the EORTC QLQ-CR38, the ISR group had significantly higher scores of general gastrointestinal symptoms and weight loss in the symptom scales than the taTME group (P<0.05). [Conclusion] Both taTME and ISR are safe for low rectal cancer. They show comparable postoperative recovery of anal function, but taTME is associated with relatively better postoperative quality of life.